Disparities in Rates of Fusions in Lumbar Disc Pathologies. Issue 2 (March 2022) - Kim, Soobin; Ryoo, James S.; Ostrov, Philip B.; Reddy, Abhinav K.; Behbahani, Mandana; Mehta, Ankit I.
Study Design: Retrospective cohort study. Objective: To identify disparities in surgical decision making for lumbar disc pathologies based on patient demographics, hospital characteristics, and temporal characteristics of admission. Methods: A retrospective analysis of patients admitted for surgical intervention of disc herniation or degeneration was performed to observe the effect of demographic, hospital, and admission-related factors on the decision to perform an isolated decompression or decompression with single level fusion using the National Inpatient Sample. Results: Of 84 953 patients with lumbar disc pathologies, 69 975 patients were treated electively, and 14 978 patients were treated nonelectively. Hispanic and Asian/Pacific Islander patients were less likely to receive a fusion for elective cases compared with White patients (odds ratio [OR] 0.88, P = .004; OR 0.70, P < .001, respectively). In elective cases, privately insured and self-paying patients were less likely to receive a fusion compared with Medicare patients (OR 0.83, P < .001; OR 0.66, P < .001, respectively), while this effect was limited to self-pay patients in nonelective cases (OR 0.44, P < .001). Urban teaching and nonteaching hospitals were less likely to perform fusions compared with rural hospitals in nonelective cases (OR 0.47, P < .001; OR 0.58, P < .001, respectively). Private for-profit hospitals were associated with higher rates of fusion in both elective and nonelective cases (OR 1.16, P = .003; OR 1.94, P < .001). Conclusion: This study illustrates disparities in the modality of surgical intervention for lumbar disc pathologies in terms of demographics, hospital characteristics, and temporal characteristics of admission. The development of more evidence-based guidelines is warranted to reduce variability seen in treatment regimens for these conditions.